PEMAAFAN REMAJA BROKEN HOME DI KOTA TOMOHON - Marunduri, Marchellus S.; Katuuk, Deitje A.; Kumaat, Theophany D. (PSIKOPEDIA, 2024)
Forgiveness is a process that affects emotional changes and a person’s attitude towards the abuser who has hurt him. This study aims to determine the process of forgiveness, factors that influence forgiveness, and forms of forgiveness in broken home adolescents in Tomohon City whose parents divorced. The method used in this study is qualitative phenomenological method. The informants used as research material amounted to two people, sampling in this study was purposive sampling, the methods used were observation and interviews. The results of this study show differences in forgiveness that occur in the two informants as well as different experiences of events and perceptions of actions committed by each parent towards the informant and also in the informant’s family which can be seen from the dimension of forgiveness by McCullough, Root, and Cohen (2006).